2002
DOI: 10.1075/term.8.1.05bar
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical refinement and representation of the causal relation

Abstract: This research looks at the complexity inherent in the causal relation and the implications for its representation in a Terminological Knowledge Base (TKB). Supported by a more general study of semantic relation hierarchies, a hierarchical refinement of the causal relation is proposed. It results from a manual search of a corpus which shows that it efficiently captures and formalizes variations expressed in text. The feasibility of determining such categorization during automatic extraction from corpora is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…"breaker voltage exceeded allowable limit"). We observed that these relations had optional causal-agents, and that they could not be conclusively classified in Barriere's taxonomy of causality [1]. When the causal-agents were specified, as in "[short-circuit in brake wiring causal-agent ] destroyed the power supply", the relations indicated the creation or destruction of events.…”
Section: Causal Relation Extractionmentioning
confidence: 89%
See 3 more Smart Citations
“…"breaker voltage exceeded allowable limit"). We observed that these relations had optional causal-agents, and that they could not be conclusively classified in Barriere's taxonomy of causality [1]. When the causal-agents were specified, as in "[short-circuit in brake wiring causal-agent ] destroyed the power supply", the relations indicated the creation or destruction of events.…”
Section: Causal Relation Extractionmentioning
confidence: 89%
“…These results also demonstrate that Wikipedia can be effectively leveraged upon as a knowledge-base for extracting domain-specific causal relations. Furthermore, we found out that some of the identified domain-specific relations were not conclusively classifiable in Barriere's taxonomy of causality [1].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other classifications of the part-whole relation have been developed by Barriere (1997Barriere ( & 2002, Markowitz, Nutter & Evens (1992), Sattler (1995) specifically for an engineering application, Uschold (1996) for ecological information systems, and Bernauer (1996) for the medical domain.…”
Section: Meronym-holonym Relationmentioning
confidence: 99%